1971
DOI: 10.1037/h0030579
|View full text |Cite
|
Sign up to set email alerts
|

The inverse relationship between shock intensity and shuttle-box avoidance learning in rats: A reinforcement explanation.

Abstract: Shock intensity (.3 or 1.6 ma.) was combined faotorially with ITI (15, 30, or 45 sec.) in a shuttle-box avoidance task (n -20/group). Following 65 avoidance trials, rats were allowed, in the absence of both shock and the CS, to jump from one compartment of the shuttle box to an adjacent safe box. The 1.6-ma. groups made significantly fewer avoidance responses than the ,3-ma. groups but jumped into the safe box with significantly shorter latencies. The latter finding is contrary to ari interpretation of the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…A decrease of fear of the warning signal after a long run of successive avoidance trials was confirmed with this method and, additionally, the maintenance of high level of fear of situational cues was shown. On the basis of these and some other data, McAllister and colleagues proposed that the effective reinforcement for an avoidance response is positively related to the amount of fear reduction occurring with termination of the CS, and negatively related to the amount of fear present after the response (D. E. McAllister et aI., 1976;W. R. McAllister, D. E. McAllister, & Douglass, 1971).…”
Section: +10mentioning
confidence: 99%
“…A decrease of fear of the warning signal after a long run of successive avoidance trials was confirmed with this method and, additionally, the maintenance of high level of fear of situational cues was shown. On the basis of these and some other data, McAllister and colleagues proposed that the effective reinforcement for an avoidance response is positively related to the amount of fear reduction occurring with termination of the CS, and negatively related to the amount of fear present after the response (D. E. McAllister et aI., 1976;W. R. McAllister, D. E. McAllister, & Douglass, 1971).…”
Section: +10mentioning
confidence: 99%
“…The interaction between these two processes may interfere with the reliable measurement of emotional responses mediated by associative learning. For example, manipulations that reduce conditioned fear -such as anxiolytic drugs [84], decreases in contextual fear conditioning [85] and reduction in shock intensity [86] -enhance the acquisition of active avoidance responses. In fact, two-way avoidance learning represents one of the oldest theoretical debates in behavioral sciences (for an elegant review of this debate, see [87]).…”
Section: Conditioned Fear and The Interaction Between Two-way Avoidanmentioning
confidence: 99%
“…E. McAllister, W. R. McAllister, & Dieter, 1976;W. R. McAllister, D. E. McAllister, & Douglass, 1971;Moyer & Korn, 1964;Scoles, 1982Scoles, /1983Theios, Lynch, & Lowe, 1966).…”
mentioning
confidence: 99%